Ενίσχυση της νοσηλευτικής εκπαίδευσης σε θέματα μεταμοσχεύσεων: Αναγκαιότητα και προοπτικές. - Μεντές, Νικόλαος Νεκτάριος; Γιάννενα, Ειρήνη; Κουτελέκος, Ιωάννης; Μπακάλης, Βησσαρίων (Nosileftiki)
Introduction: Advances in the field of transplantation have significantly increased the demands for more specialized and comprehensive patient care. Nurses play a very important role in the transplant process, both in the preoperative preparation of the patient, as well as in the postoperative support and management of immunosuppression as well as the psychosocial empowerment of patients and their families. Despite the importance of their role, there is often a lack of education and training programmes in the field of transplantation. Aim: The purpose of this literature review is to capture the current situation regarding the training of nurses on transplant issues, as well as to highlight the importance and effectiveness of targeted educational interventions, to improve the care provided to patients. Methodology: The literature was searched in the PubMed databases for the period 2019-2025, using keywords such as nursing education, organ transplantation, competency-based education, transplant nursing, e-learning, organ donation, ICU nurses and health literacy. This search resulted in 370 articles in English. The studies were selected according to specific eligibility criteria. This was followed by an analysis and synthesis of the results of the studies. Results: An analysis of the literature shows that educational interventions based on structured programs that combine both theoretical knowledge and practical practice as well as interdisciplinary cooperation, contribute substantially to the enhancement of the skills and existing knowledge of nurses in the field of transplantation. Participants in such programs reported higher levels of professional competence, a better understanding of the transplant process, and increased confidence in dealing with complex clinical conditions. At the same time, the quality of care for organ recipients was improved, through effective monitoring, prevention of complications and enhancement of therapeutic compliance. The trainings carried out promoted team collaboration among health professionals, strengthening the cohesion of the transplant team, while nursing students who participated in targeted educational programs showed more positive attitudes and higher levels of knowledge about transplants. Conclusions: Strengthening nursing education in the field of transplantation is a critical factor in improving the care of recipients and the support of the health system. The development of certified programs and their integration into both undergraduate and continuing nurse education is imperative.